INTEGRATED CONTROL OF CABAGGE PESTS Plutella xylostella (L) AND Crocidolomia binotalis (Z) BY RELEASE OF IRRADIATED MOTHS AND THE PARASITOID Diadegma semiclausums(H) UNDER FIELD CAGE AND A SMALL AREA CONDITIONS - Sutrisno, Singgih (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2013)
The impact of the release of irradiated Diamondback moth (DBM) Plutella xylostella (L) with a dose of 200 Gy was studied in field cage experiments by releasing of irradiated and untreated DBM at a 9:1 ratio . Releasing male and female (F-1) of irradiated DBM caused a considerable level of sterility in the subsequent generations. The sterility level in those respective generations were 73.03% and 73.30%,while the release of the F-1 male only induced a level of sterility of about 55.40% and 56.44%.Inundative releases of irradiated males caused the level of sterility to reach about 44.78% and 68.01% in F-1 and F-2 respectively. Them effect of the release of irradiated male Cabbage webworm (CWW) moths Crocidolomia binotalis (Z), and the release of both sexes on the population were studied under laboratory cage conditions. There was a significant difference between the) effects of releasing irradiated male only and both sexes at a level of F ≤ 0.001 ,where the percentage of egg hatch were 22.78% and 24.75% respectively in the F-1 and F-2 generations. The effects of combining two tactics, inherited sterility and the release of parasitoid Diadegma semiclausums (H) for controling DBMs were studied.The pupal viability in the F-1 generation was 32.5% as compared to the untreated DBMs. The impacts of respective single tactic the release of F-1 males and parasitoid D. semiclausums on the pupal viability were 57.5% and 81%. The effects of the release of substerile insects in a small area of about 1000 m2 located at an isolated area in the forest in Malang, East Jawa was found that average number of moths caught per week from first to the fifth month at the release area was about 89.42% as compared to those at the control area. The highest level of parasitation of D. semiclausums was found in the second instar larvae of DBMs. Population growth of parasitoid D. semiclausums from the first generation to the eleventh generation increased till to the fifth generation larvae, than declined to the eleventh generation.